1976
DOI: 10.1161/01.cir.54.4.603
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of hyperosmotic mannitol in myocardial ischemia and necrosis.

Abstract: Morphologic and hemodynamic changes that occur following coronary occlusion are examined. The effectiveness of hyperosmotic mannitol in lessening the extent of myocardial damage is assessed and mechanisms for its action discussed. Forty and 60 min of coronary vascular occlusion followed by 15 and 45 min of reflow were associated with a persistence of ischemia following reflow of blood, as established by infusions of silastic into the aortic root. Electron microscopic studies demonstrated myocardial and endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
47
1
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 7 publications
6
47
1
1
Order By: Relevance
“…Thus, the finding that the administration of hypertonic mannitol (15) and of fluorocarbons (73) during reperfusion augment myocardial salvage is of great interest because potentially these agents could be infused directly into the infarct-related coronary artery when the latter is opened by the intracoronary administration of a thrombolytic agent or by means of transluminal angioplasty. The demonstration, in experimental animals, that the deleterious effects of reperfusion are related importantly to the action of oxygen-derived free radicals and that these effects can be reduced or even prevented with scavengers offree radicals is intriguing.…”
Section: Oxygen-derivedfree Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the finding that the administration of hypertonic mannitol (15) and of fluorocarbons (73) during reperfusion augment myocardial salvage is of great interest because potentially these agents could be infused directly into the infarct-related coronary artery when the latter is opened by the intracoronary administration of a thrombolytic agent or by means of transluminal angioplasty. The demonstration, in experimental animals, that the deleterious effects of reperfusion are related importantly to the action of oxygen-derived free radicals and that these effects can be reduced or even prevented with scavengers offree radicals is intriguing.…”
Section: Oxygen-derivedfree Radicalsmentioning
confidence: 99%
“…Similar considerations apply to patients in whom the subendocardium also Receivedfor publication 10 July 1985. is most susceptible to ischemic damage. It (15,16). However, in a recent study (17), we found that administration of a calcium channel antagonist at the time of coronary reperfusion did not limit infarct size, a finding which does not support the suggestion that reperfusion causes necrosis ofreversibly injured myocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial ischemia produces alterations in cell membrane integrity that develop early during the course of experimental ischemic myocardial injury (1)(2)(3)(4)(5)(6)(7)(8). Such alterations in cell membrane permeability appear to precede the development of irreversible cellular injury (1,2,8); some investigators have even suggested that these alterations in membrane permeability play a causal role in the development of irreversible cellular injury (1,2,5,6,8).…”
mentioning
confidence: 99%
“…Such alterations in cell membrane permeability appear to precede the development of irreversible cellular injury (1,2,8); some investigators have even suggested that these alterations in membrane permeability play a causal role in the development of irreversible cellular injury (1,2,5,6,8).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] However, such clear-cut therapeutic benefit in human myocardial infarction has not been demonstrated.7 -3 One reason for this may be limitations in the techniques suitable for objective documentation of myocardial salvage in man. Recently, radionuclide techniques such as multigated cardiac blood pool imaging have been proposed for noninvasive assessment of global cardiac performance at the patient's bedside, thereby providing functional estimates of myocardial salvage.…”
mentioning
confidence: 99%